Representation of the moderate education curriculum in Indonesia; integration of NU and Muhammadiyah thought - Sumiarti; Azizah, Intan Nur (UIN Salatiga, 2024)
This study aims to analyze the curricula of NU and Muhammadiyah educational institutions, focusing on their contributions to supporting moderate Islamic education. The research was conducted in Central Java, Indonesia, using a descriptive qualitative method. Data collection techniques included classroom observations, in-depth interviews with school principals and teachers, as well as an analysis of curriculum documents and teaching materials. The findings reveal fundamental differences and similarities between the two curricula. NU's curriculum is rooted in the concept of